2012
DOI: 10.1111/j.1545-5300.2012.01420.x
|View full text |Cite
|
Sign up to set email alerts
|

Couple Relationship Education at the Transition to Parenthood: A Window of Opportunity to Reach High‐Risk Couples

Abstract: This study evaluated if the transition to parenthood is a window of opportunity to provide couple relationship education (CRE) to new parents at high risk for future relationship problems. Fifty-three percent of eligible couples approached agreed to participate in CRE and of these 80% had not previously accessed CRE. Couples were a broad representative of Australian couples having their first child, but minority couples were underrepresented. A third of couples had three or more risk factors for future relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 73 publications
4
41
0
3
Order By: Relevance
“…Similar to our findings that seeking formal help was perceived as 'unnecessary' , this perception of 'normality' has resulted in women enduring violence without any (formal) help. Couples typically do not perceive lowlevel IPV as problematic in their relationship however, research has shown that they are at high risk for future relationship dissatisfaction and instability [63,86]. Additionaly, we found that more than half of our participants were in the precontemplation phase according to the model on readiness to change [87], which implies that they were minimising or denying the IPV.…”
Section: Help-seeking Behaviourmentioning
confidence: 53%
“…Similar to our findings that seeking formal help was perceived as 'unnecessary' , this perception of 'normality' has resulted in women enduring violence without any (formal) help. Couples typically do not perceive lowlevel IPV as problematic in their relationship however, research has shown that they are at high risk for future relationship dissatisfaction and instability [63,86]. Additionaly, we found that more than half of our participants were in the precontemplation phase according to the model on readiness to change [87], which implies that they were minimising or denying the IPV.…”
Section: Help-seeking Behaviourmentioning
confidence: 53%
“…Parejas pertenecientes a población vulnerable y de riesgo: En los últimos años se han sido implementados exitosamente estos programas en población desventajadas (Ooms et al, 2004;Ooms, 2007), los cuales pueden también operar en el apoyo a la transición a la parentalidad (Petch, Halford, Creedy, y Gamble, 2012). En la aplicación del programa PREP masivamente en el estado de Oklahoma en Estados Unidos con familias pobres, se constató que la efectividad de estas intervenciones aumenta significativamente con sesiones de reforzamiento (Ooms, 2007).…”
Section: La Realidad En Chile Y Aportes Potenciales Al Paísunclassified
“…Halford and Bodenmann (2013) also argue that longer term benefits of RE are more easily detected in couples at higher risk of relationship distress (e.g., those with family-of-origin parental divorce or violence), as these couples show a larger natural decline in satisfaction over time, in contrast to lower risk couples who might remain stable even in the absence of RE. Consistent with this proposition of a selective effect of RE, risk moderates the effects of RE with moderate to large effects evident for high-risk couples two to four years after RE (Allen, Rhoades, Stanley, Loew, & Markman, 2012;Halford, Sanders & Behrens, 2001;Petch, Halford, Creedy, & Gamble, 2012). Some couples utilise relationship self-help books in order to enhance their relationship in a low-cost and private setting.…”
Section: Relationship Education -Research With Civilian and Military mentioning
confidence: 71%
“…A larger trial of the program with 250 expectant couples showed similar declines on negative communication for intervention couples. There was also less decline in satisfaction across three years for women in the CCP condition relative to control, although this effect was just in high-risk couples (Petch, Halford, Creedy, & Gamble, 2012). A version of Couple CARE was also developed for couples dealing with hazardous alcohol consumption in one or both partners (Bouma, Halford, & Young, 2004).…”
Section: Relationship Education -Research With Civilian and Military mentioning
confidence: 99%
See 1 more Smart Citation